Heavy Metal Levels in Beans (Vigna unguiculata) in Selected Markets in Ibadan, Nigeria (2018)
Aim: Beans play a significant role in human diet especially in developing nations like Nigeria which happens to be the largest producer and consumer of beans in the world. To ensure food safety, heavy metal levels need to be monitored on regular basis to control human exposure through dietary intake. Methodology: 72 Samples of brown beans (Oloyin and Drum) were obtained from three different markets in Ibadan, Nigeria. The markets were Ayeye Market. Bodija Market and Oja-Oba Market. Powdered samples were digested with nitric acid. Extract from the digest were analyzed for Lead (Pb) and Cadmium (Cd) using Buck Scientific Atomic Absorption Spectrometer. Results: Concentration of Cd and Pb ranged from 0.00 to 0.01 mg/kg and 0.00 to 1.52 mk/kg respectively. The results of this research indicated levels of Cadmium and Lead within safe limit, hence human health is not at danger. Conclusion: Efforts need to be made in total elimination of heavy metal in the beans because human health is at risk due to the effects of their bioaccumulation in the body